Effects of porang glucomannan combined with a high-protein diet on oxidative stress, inflammation, and aging markers in D-galactose-induced rats - Safitri, Azizah H.; Sayyida, Rahmata A.; Setyawan, Sigit; Tyagita, Nurina (Narra J, 2025)
Aging is a predominant risk factor for several diseases associated with reduced life expectancy. To address this risk factor, several studies have proposed the combined use of porang glucomannan and a high-protein diet to improve various aging markers. The aim of this study was to determine the effects of porang glucomannan and high-protein combination diet as an anti-aging agent. An experimental study using a post-test-only control group design was conducted using Sprague Dawley white rats. The animals were randomly divided into four groups with different treatments as follows: normal control, D-galactose, high-protein diet, and a combination of porang glucomannan and high-protein combination diet. Blood samples were then collected from the ophthalmic vein on day 58 for biomarker measurement using the enzyme-linked immunosorbent assay (ELISA) method. The parameters measured were superoxide dismutase (SOD), malondialdehyde (MDA), interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), insulin growth factor-1 (IGF-1), NOD-like receptor family pyrin domain-containing protein 3 (NLRP3), growth differentiation factor-11 (GDF11), and α-Klotho levels. The results showed that the combination of porang glucomannan and high-protein diet could improve oxidative stress, inflammation, and aging markers. The analysis of variance (ANOVA) test followed by post-hoc least significant difference (LSD) showed significant differences between the combination diet and high protein group (p<0.0001). In addition, the average levels of oxidative stress markers (SOD and MDA) in porang glucomannan and high-protein combination group were improved significantly. Similar results were also obtained for inflammatory markers (IL-6 and TNF-α) and aging markers (NLRP3, IGF-1, GDF-11, and α-Klotho). The mean NRLP-3 levels in glucomannan and high-protein combination group were not significantly different compared to control. The study highlights that the combination of porang glucomannan and a high-protein diet effectively improved various aging markers.